Advancing primary and community care for persons with spinal cord injury: Key findings from a Canadian summit. (3rd March 2020) - Milligan, James; Lee, Joseph; Smith, Matt; Donaldson, Lindsay; Athanasopoulos, Peter; Bassett-Spiers, Kent; Howcroft, Jeremy; Howcroft, Jennifer W.; Jeji, Tara; Joshi, Phalgun B.; Mehan, Upender; Noonan, Vanessa
Abstract : Context: Persons with spinal cord injury (SCI) experience significant challenges when they access primary care and community services. Design : A provincial summit was held to direct research, education, and innovation for primary and community care for SCI. Setting: Toronto, Ontario, Canada. Participants: Key stakeholders ( N  = 95) including persons with SCI and caregivers, clinicians from primary care, rehabilitation, and specialized care, researchers, advocacy groups, and policy makers. Methods : A one-day facilitated meeting that included guest speakers, panel discussions and small group discussions was held to generate potential solutions to current issues related to SCI care and to foster collaborative relationships to advance care for SCI. Perspectives on SCI management were shared by primary care, neurosurgery, rehabilitation, and members of the SCI community Outcome Measures: Discussions were focused on five domains: knowledge translation and dissemination, application of best practices, communication, research, and patient service accessibility. Results : Summit participants identified issues and prioritized solutions to improve primary and community care including the creation of a network of key stakeholders to enable knowledge creation and dissemination; an online repository of SCI resources, integrated health records, and a clinical network for SCI care; development and implementation of strategies to improve care transitions across sectors; implementation of effective care models and improved access to services; and utilization of empowerment frameworks to support self-management. Conclusions : This summit identified priorities for further collaborative efforts to advance SCI primary and community care and will inform the development of a provincial SCI strategy aimed at improving the system of care for SCI.